Bureaucratic Neutrality in Electoral Contests and Its Democratic Implications: A Systematic Literature Review and Analysis - Awaluddin Hasrin; Lisbet Situmorang; Lalu Murdi (Jurnal Sosial Indonesia, 2026)
This research explores the concept of bureaucratic neutrality and its significant role in maintaining electoral integrity, particularly in Indonesia. Political dynasties, with their monopolization of political power, present a major challenge to the democratic process, as they limit electoral fairness and hinder the transparency of election outcomes. The study aims to analyze the relationship between bureaucratic neutrality and democratic processes, emphasizing the need for impartiality in electoral administration. The research methodology includes a systematic literature review, focusing on key studies that examine the impact of political interference and partisanship on electoral processes. The findings suggest that the erosion of bureaucratic neutrality due to political pressures and patronage networks compromises the legitimacy of elections, leading to voter disillusionment and reduced participation. Furthermore, the study reveals that maintaining neutrality is crucial for fostering public trust and ensuring that elections reflect the true will of the people. Implications of the research emphasize the need for stronger institutional frameworks, legal reforms, and independent oversight bodies to protect the neutrality of electoral bureaucrats. The study highlights the importance of transparency, decentralization, and political diversity in creating a fair and competitive electoral system, which is essential for the consolidation of democracy in Indonesia.